Comparison of Activity and Participation, and Mental and Physical Functions of Immediate Post-Acute and Distant Post-Acute Adults with Chronic Cardiac Conditions. Issue 4 (1st October 2021) - Kim, Young Joo; Swift, Damon L.; Houmard, Joseph A.
Abstract: This study compared activity participation, and mental and physical functions of two different groups of adults with chronic cardiac conditions. Eleven participants were assessed at the immediate post-acute stage and 26 participants were at the distant post-acute stage. Participants at distant post-acute were significantly more physically active ( p < .001), more activity-limited in cognition-related activities ( p = .035) and reported more depressive symptoms than immediate post-acute ( p = .046). No significant difference in participation level was found. More attention to functional cognition and depressive symptoms at immediate post-acute and individualized approaches to remove participation barriers in complex activities at distant post-acute are likely needed for adults with chronic cardiac conditions.